Unraveling disparities in ventricular fibrillation-related mortality among US adults(>25 years) with DM. A longitudinal analysis of Gender and geographic inequities using CDC WONDER (1999-2020) - Faiza Ikram (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: Ventricular fibrillation (VF) is a fatal arrhythmia, with adults diagnosed with diabetes mellitus (DM) facing heightened mortality risk. Despite advances in cardiac and diabetes care, improvements have not been uniformly distributed. Persistent disparities by sex and geography remain insufficiently examined in national, long-term studies. Objective: To evaluate temporal trends and disparities in VF-related mortality among U.S. adults aged ≥25 years with DM from 1999 to 2020, with emphasis on sex and geographic variations. Methodology: Data were extracted from the CDC WONDER Multiple Cause of Death database, identifying decedents aged 25–85+ with both VF (ICD-10: I49.0) and DM (ICD-10: E10–E14) listed. Age-adjusted mortality rates (AAMRs) per 100,000, standardized to the 2000 U.S. population, were calculated and stratified by sex, urbanization level, census region, and state. Join point regression was used to analyze trends and estimate annual percentage change (APC) with 95% confidence intervals. Results: Between 1999 and 2020, ventricular fibrillation contributed to 35,339 diabetes-related deaths among adults aged ≥25 years, with most occurring in medical facilities [80.06%]. The age-adjusted mortality rate (AAMR) declined from 1.42 [95% CI: 1.37–1.48] in 1999 to 0.64 [95% CI: 0.61–0.67] in 2020, with an average annual percent change (AAPC) of −4.16 [−4.72 to −3.60] (p < 0.000001). Men had higher AAMRs than women [1.04 vs. 0.47] (Men: AAPC −3.44; Women: AAPC −4.32; both p < 0.000001). Regional AAMRs varied [West: 0.82; Midwest: 0.74; South: 0.73; Northeast: 0.6]. Rural deaths [6,888; 19.3%] were four times lower than urban deaths [28,451; 80.5%], though nonmetropolitan areas had higher AAMRs [0.82; 95% CI: 0.80–0.84] than metropolitan areas [0.71; 95% CI: 0.71–0.72]. Mortality rates declined steadily over time, with Tennessee showing the highest and Nevada the lowest rates. Conclusion: Despite overall declines in VF-related mortality among adults with diabetes, disparities persist. Men, those in nonmetropolitan areas, and residents of certain regions—especially the South and West—continue to face higher mortality. Targeted interventions are needed to address these enduring inequities.